The Effect of Return on Asset (ROA) and Net Profit Margin (NPM) on Profit Growth at PT Unilever Indonesia Tbk for the 2005-2023 - Mira Santika Dewi; Nia Kurniasari (Formosa Journal of Social Sciences (FJSS), 2024)
Examining the "Effect of Return on Asset (ROA) and Net Profit Margin (NPM) on Profit Growth at PT Unilever Indonesia Tbk for the years 2005- 2023" is the main objective of this study initiative. A quantitative technique based on a descriptive associative       methodology            is         used   in the investigation. The data utilised in this analysis comes from PT Unilever Indonesia Tbk's annual financial         statements,    specifically    a non- probability sample of 19 years' worth of data from 2005 to 2023. This research used SPSS Version 27.0 to do multiple linear regression analysis. The study found that ROA has a 0.000 significance level, meaning it contributes considerably to Profit Growth. At the 0.012 level of significance, NPM is partly responsible for Profit Growth. The combined effect of ROA and NPM           on Profit Growth was statistically significant (0.000) when tested in a F test